Extraction and Characterisation of Avocado Seed Starch, and Its Blend with Enset Cellulosic. (22nd October 2022) - Alemu, Negese; Balakrishnan, Subramanian; Debtera, Baru
Abstract : Avocado seed starch was extracted to prepare a biodegradable plastic film with enset cellulosic reinforcement and glycerol plasticiser. The characterisations were made in detail. Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimeter (DSC), scanning electron microscopy (SEM), X-ray diffraction (XRD), rheometer, and Rapid Visco Analyser (RVA) techniques were employed to characterise the physicochemical properties of avocado seed starch, enset cellulosic, and the blend. Starch and enset cellulosic extraction yields are 18.3 ± 0.02% and 67.5 ± 0.08%, respectively. As a result, avocado seed starch and enset cellulosic blend can be used as alternative raw materials to develop biodegradable plastics.